(untitled) (Journal of Computational Mathematics, 2021)
We consider the singular perturbation problem -ε^2u"+μ b(x,u)u'+c(x,u)=0,u(0),u(1) given with two small parameters ε and μ , μ =ε^1+p,p>0. The problem is solved numerically by using finite difference schemes on the mesh which is dense in the boundary layers. The convergence uniform in ε is proved in the discrete L^1 norm. Some convergence results are given in the maximum norm as well.